2020
DOI: 10.11591/ijece.v10i3.pp3307-3314
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on techniques used to recognize and identifying the Human emotions

Abstract: Facial expression is a major area for non-verbal language in day to day life communication. As the statistical analysis shows only 7 percent of the message in communication was covered in verbal communication while 55 percent transmitted by facial expression. Emotional expression has been a research subject of physiology since Darwin’s work on emotional expression in the 19th century. According to Psychological theory the classification of human emotion is classified majorly into six emotions: happiness, fear,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The Viola and Jones face locator has become the deformity standard to assemble fruitful face recognition in ascertaining emotions progressively, in any case, it creates a high bogus positive (identifying a face when there is none) and bogus negative rate (not recognizing a face that is available) when straightforwardly applied to the information picture [8]. Different techniques and algorithms for emotional analysis considered from different researchers with accuracy analysed by authors [9].…”
Section: Related Workmentioning
confidence: 99%
“…The Viola and Jones face locator has become the deformity standard to assemble fruitful face recognition in ascertaining emotions progressively, in any case, it creates a high bogus positive (identifying a face when there is none) and bogus negative rate (not recognizing a face that is available) when straightforwardly applied to the information picture [8]. Different techniques and algorithms for emotional analysis considered from different researchers with accuracy analysed by authors [9].…”
Section: Related Workmentioning
confidence: 99%
“…Fusing HOG and CNN [67] 97.01% FaeveLiveNet based on Inception-RsNet [68] 98.0% Deep Covariance Trajectories [69] 98.4% Evolutional Spatial-Temporal Networks [70] 98.5% Hybrid feature descriptor [71] 98.5% Secondary Information aware Network [72] 99.5% [74] 91.81% Feature extraction based on gabor filter [75] 93.4% DNN based on residual blocks [76] 95.23% Proposed method 99.84%…”
Section: Model Fusionmentioning
confidence: 99%
“…Machine learning methods such as k-nearest neighbor (KNN) or support vector machine (SVM) have been widely used to solve this problem. However, previous study shows that neural network algorithm could achieved reliable accuracy even not the highest among hidden Markov model, AdaBoost, and SVM [9]. In other several studies found that the level of accuracy possessed by these algorithms is classified as lower when compared to the neural network (NN) model [10]- [12].…”
Section: Introductionmentioning
confidence: 95%